Immunomodulatory action of new curcumin analogue [2,6-BIS(2,5-dimethoxybenzylidene) cyclohexanone] on major inflammatory mediator expression in activated macrophage and synovial fibroblast cells - Lee, Ka Heng (2012)
Rheumatoid arthritis is a chronic inflammatory disease characterized by abnormal immune phenomena involving macrophage and synovial fibroblast resulting in progressive joints destruction. In this study, a series of newly synthesized curcumin diarylpentanoids were screened for their anti-inflammatory properties by evaluating the nitric oxide (NO) inhibitory activity upon activated macrophages in vitro. The preliminary screening results have shown that curcumin-like BDMC33 [2,6-bis(2,5-dimethoxybenzylidene) cyclohexanone] exerted improved nitric oxide inhibitory activity (IC50 value = 13.66 ± 0.61 μM) as compared to curcumin (IC50 value = 27.13 ± 5.58). Therefore, we further investigated the immunomodulatory action of BDMC 33 on two cellular systems which are IFN-y/LPS-stimulated macrophages (RAW 264.7) and PMA-stimulated synovial fibroblast (HIG-82). BDMC33 was found to inhibit the NO and PGE2 production through down-regulation of iNOS and COX-2 expression in activated macrophages without altering its enzyme activities, respectively. In addition, effect of BDMC33 was observed to inhibit production of TNF-α and IL-1β at the protein and gene expression level. Further studydemonstrated that the inhibitory activities of BDMC33 was mediated by interfering in NF-KB signal transduction pathway, includes inhibition of NF-KB DNA binding activities and p65 NF-KB nuclear translocation as well as prevent rapid phosphosrylation and degradation of IKB subunit. Moreover, DNA binding activities of AP-1 also appear to be inhibited by BDMC33 through attenuation of ERK1/2 and JNK1/2 phosphorylation. On the other hand, BDMC33 significantly inhibited the MMP-9 activities as well as collagenase activities via suppression of MMP-1 expression upon activated synovial fibroblast. Moreover, BDMC33 strongly suppressed MMP-3 gene expression as well as inhibited COX-2 and IL-6 inflammatory gene expression in activated synovial fibroblast. The underlying mechanism of BDMC33 on synovial fibroblast was also mediated via NF-KB signaling pathway; as p65 NF-KB nuclear translocation and NF-KB DNA binding activity are being attenuated. Collectively, the experimental data suggested that the immunomodulatory action of BDMC33 is attributed through interference in inflammatory mediator expression of both macrophages and synovial fibroblast, which could lead to its possibility into future evaluation of the in vivo or pre-clinical study.